Changes in peripheral immune cells after intraoperative radiation therapy in low-risk breast cancer. (2nd October 2020) - Linares-Galiana, Isabel; Berenguer-Frances, Miguel Angel; Cañas-Cortés, Rut; Pujol-Canadell, Monica; Comas-Antón, Silvia; Martínez, Evelyn; Laplana, Maria; Pérez-Montero, Héctor; Pla-Farnós, María Jesús; Navarro-Martin, Arturo; Nuñez, Miriam; Both, Brigitte; et al.
Abstract: A detailed understanding of the interactions and the best dose-fractionation scheme of radiation to maximize antitumor immunity have not been fully established. In this study, the effect on the host immune system of a single dose of 20 Gy through intraoperative radiation therapy (IORT) on the surgical bed in low-risk breast cancer patients undergoing conserving breast cancer has been assessed. Peripheral blood samples from 13 patients were collected preoperatively and at 48 h and 3 and 10 weeks after the administration of radiation. We performed a flow cytometry analysis for lymphocyte subpopulations, natural killer cells (NK), regulatory T cells (Treg) and myeloid-derived suppressor cells (MDSCs). We observed that the subpopulation of NK CD56 +high CD16 + increased significantly at 3 weeks after IORT (0.30–0.42%, P  < 0.001), while no changes were found in immunosuppressive profile, CD4 + CD25 + Foxp3 + Helios + Treg cells, granulocytic MDSCs (G-MDSCs) and monocytic MDSCs (Mo-MDSCs). A single dose of IORT may be an effective approach to improve antitumor immunity based on the increase in NK cells and the non-stimulation of immunosuppressive cells involved in immune escape. These findings support future combinations of IORT with immunotherapy, if they are confirmed in a large cohort of breast cancer patients.